(untitled) (World Bulletin of Management and Law, 2023)
The article discusses the problems of achieving targets in the field of digitalization in transport logistics of the Republic of Uzbekistan. Measures are proposed to increase efficiency and optimize logistics processes. A conclusion is drawn about the importance of the transport and economic balance, the introduction of information tools that allow monitoring and successfully predicting the subsequent development of demand for logistics services in order to implement an effective planning system